2015
DOI: 10.1091/mbc.e15-03-0159
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear-localized CTP:phosphocholine cytidylyltransferase α regulates phosphatidylcholine synthesis required for lipid droplet biogenesis

Abstract: Phosphatidylcholine (PC) synthesis by the CDP-choline pathway in mammalian cells regulates lipid droplet size and triacylglycerol storage. Mechanistically this involves increased CCTα expression and translocation to the nuclear envelope. CCTα regulates the PC synthesis required for lipid droplet biogenesis without associating with the surface of the particle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(70 citation statements)
references
References 40 publications
4
59
3
Order By: Relevance
“…In contrast to the results using insect cells [131], CCTa did not translocate from the nucleus to the surface of LDs in mammalian adipocytes or oleate-treated cultured cells [133]. Endogenous and epitope tagged CCTa was observed on the nuclear envelope (NE) or cytoplasmic membranes during LD biogenesis, indicating these are the membranes on which the enzyme regulates PC synthesis and LD size.…”
Section: Ccta Regulates Lipid Droplet Sizecontrasting
confidence: 87%
See 1 more Smart Citation
“…In contrast to the results using insect cells [131], CCTa did not translocate from the nucleus to the surface of LDs in mammalian adipocytes or oleate-treated cultured cells [133]. Endogenous and epitope tagged CCTa was observed on the nuclear envelope (NE) or cytoplasmic membranes during LD biogenesis, indicating these are the membranes on which the enzyme regulates PC synthesis and LD size.…”
Section: Ccta Regulates Lipid Droplet Sizecontrasting
confidence: 87%
“…Endogenous and epitope tagged CCTa was observed on the nuclear envelope (NE) or cytoplasmic membranes during LD biogenesis, indicating these are the membranes on which the enzyme regulates PC synthesis and LD size. CCT localization in insect vs mammalian cells may differ due to the surface monolayer composition of LDs, which is PC-rich in mammalian cells but is PE-rich in insect cells [133]. Other questions remain regarding the role of CCT activation during LD biogenesis, such as why such a robust response is required when <5% of cellular PC is on the surface of LDs, and how PC that is synthesized in the ER (final step catalyzed by CEPT; Fig.…”
Section: Ccta Regulates Lipid Droplet Sizementioning
confidence: 99%
“…Indeed, a mutation affecting binding of CCT∝ to LDs results in lipodystrophy, suggesting that LD binding is important for its metabolic function [68]. Aitchison et al failed to observe CCT∝ binding to LDs in cultured murine adipocytes [69], perhaps owing to insufficient PC deficiency on LD surfaces in their system.…”
Section: Targeting Of Class II Ld Proteins From the Cytosolmentioning
confidence: 99%
“…CCTα was recruited to the surface of expanding LDs in murine macrophages [69], suggesting that the role of CCT in LD growth is conserved from insects to mammals. However, a recent study found that while CCTα activity was important for LD expansion, CCTα was not recruited to LDs in differentiating 3T3-L1 adipocytes or a wide variety of non-adipocyte cell types incubated with oleate [77]. One explanation that was proposed for these apparent contradictory results is that Drosophila S2 cells have significantly different phosphatidylcholine: phosphatidylethanolamine ratios, resulting in more recruitment of CCT to LDs during LD expansion [77].…”
Section: Establishing the Ld Proteomementioning
confidence: 99%
“…However, a recent study found that while CCTα activity was important for LD expansion, CCTα was not recruited to LDs in differentiating 3T3-L1 adipocytes or a wide variety of non-adipocyte cell types incubated with oleate [77]. One explanation that was proposed for these apparent contradictory results is that Drosophila S2 cells have significantly different phosphatidylcholine: phosphatidylethanolamine ratios, resulting in more recruitment of CCT to LDs during LD expansion [77]. Irrespective of the site of CCT action, the subsequent and final step in phosphatidylcholine synthesis is mediated by choline phosphotransferase (hCPT1, Golgi localized) or choline/ethanolamine phosphotransferase 1 (hCEPT, ER and nuclear envelope localized) [78].…”
Section: Establishing the Ld Proteomementioning
confidence: 99%